Restoration of portal flow with varix in liver transplantation for patients with total portal vein thrombosis: An effective strategy in the largest center experience. Issue 6 (19th April 2021) - Ravaioli, Matteo; Prosperi, Enrico; Pinna, Antonio; Siniscalchi, Antonio; Fallani, Guido; Frascaroli, Giacomo; Maroni, Lorenzo; Odaldi, Federica; Serenari, Matteo; Cescon, Matteo
Abstract: Introduction: Postoperative complications and worse prognosis still burden liver transplantations (LT) with complex portal vein thrombosis (CPVT). When an engorged left gastric vein (LGV) is present, the portal inflow is restorable with an anastomosis between the graft portal vein and the LGV of the recipient. We analyzed short‐ and long‐term results of this procedure in 12 LT with CPVT. Methods: Between 2005 and 2019, 55 patients with CPVT underwent LT. We applied this technique in 12 patients. In six cases, we placed a vascular graft to obtain a tension‐free structure. We evaluated patency, short‐ and long‐term results. Results: No intraoperative complication was observed. The median duration of LT, blood transfusion, deceased donor age, and MELD score of the recipients were 7 h, 1250 mL, 72 years, and 19. Seven patients were affected by hepatocellular carcinoma. No major complications or PVT recurrence were observed. One patient required a liver re‐transplantation for primary non‐functioning syndrome. The mean hospital stay was 20 days. The actuarial patient survival was 85% with a mean FU of 4 years. The two late deaths were due to hepatocellular carcinoma recurrence and sepsis for cholangitis. Conclusions: This technique in presence of both CPVT and engorged LGV is feasible and safe for patients, with good short‐ and long‐term results.